Post-Nuptial Agreements in Cross-Border Marriages Under Indonesian Law: Analyzing Constitutional Court Decision 69/2015 and Its Implications for Matrimonial Property Rights - I Gede Mahendra Putra; Ni Ketut Ardani (CV. Publikasi Indonesia, 2026)
The increasing prevalence of cross-border marriages necessitates robust legal frameworks governing matrimonial property rights, particularly regarding post-nuptial agreements. Indonesia's Constitutional Court Decision No. 69/PUU-XIII/2015 marked a significant departure from traditional restrictions by permitting post-nuptial agreements, a development with profound implications for mixed marriages involving Indonesian nationals and foreign spouses. This research examines the legal consequences of post-nuptial agreements in cross-border marriages under Indonesian law, analyzing how this constitutional development interacts with property ownership restrictions, citizenship regulations, and private international law principles. Employing normative legal research methodology with comparative, statutory, and case-law approaches, this study analyzes Indonesian marriage law (Law No. 1/1974 as amended by Law No. 16/2019), citizenship law (Law No. 12/2006), and agrarian restrictions, comparing these with the Netherlands, Singapore, and Australia. The research reveals that while Constitutional Court Decision 69/2015 expanded spousal autonomy by permitting agreements to be concluded at any time during the subsistence of marriage rather than exclusively before marriage, implementation challenges persist due to inadequate harmonization between marriage law, property law, and immigration regulations. The findings demonstrate critical gaps in legal certainty regarding the retroactive application of post-nuptial agreements, recognition across jurisdictions, and their effectiveness in navigating foreign ownership restrictions on Indonesian land. This study contributes to international family law scholarship by providing a comprehensive English-language analysis of Indonesia's post-nuptial agreement framework in cross-border contexts, offering recommendations for legislative reform aligned with private international law standards.